Speculative Equilibrium with Differences in Higher-Order Beliefs - Han, Jungsuk; Kyle, Albert S. (Management Science, 2018)
Modest differences in higher-order beliefs may have large price effects. We generalize a standard rational expectations equilibrium model with different information by allowing differences in higher-order beliefs. Investors have possibly different dogmatic beliefs about the mean, different dogmatic beliefs about other investors’ beliefs, and so on for higher and higher orders of beliefs. Even when every investor’s first-order expectations are unbiased, overvaluation results when investors have inconsistent higher-order beliefs that their own expectations are more optimistic than average. This lack of common knowledge destabilizes prices in an unbounded manner as market liquidity disappears. This paper was accepted by Gustavo Manso, finance.